Cell-free transcription and translation of Na,K-ATPase alpha and beta subunit cDNAs. - Cayanis, E; Bayley, H; Edelman, I (1990)
Synthetic mRNAs (i.e. cRNA alpha and cRNA beta) were obtained by cell-free transcription of M13 KS(+) (Bluescript) expression vectors which contained the entire coding region of the alpha or beta subunits of lamb kidney Na,K-ATPase. Translation in reticulocyte lysates of cRNA alpha yielded full length alpha polypeptide, as well as a limited array of immunoprecipitable lower molecular weight products. cRNA beta yielded a single immunoprecipitable full length polypeptide. Association of the alpha polypeptide with the microsomal membranes was obtained only co-translationally. Fifteen to 50% of the membrane-associated alpha subunit was resistant to extraction with alkali. The resistance of a 29-kDa fragment to trypsinolysis indicated that the alpha subunit was inserted into microsomal membranes. In the presence of dog pancreatic microsomes, the beta polypeptide was glycosylated as indicated by the appearance of three higher molecular weight polypeptides that were sensitive to endoglycosidase H and bound to Concanavalin A. The beta subunit was predominantly translocated into the lumen of the endoplasmic reticulum since 90% of the mass of the membrane-associated beta polypeptide was resistant to trypsin (i.e. reduced in size from 40 kDa to 37.5 kDa), and 95% of all of the beta chains were resistant to extraction with alkali. Neither the alpha nor the beta subunits have NH2-terminal leader signal sequences, but both may require the signal recognition receptor for membrane insertion, as evidenced by inhibition of incorporation of both subunits into microsomes pretreated with N-ethylmaleimide. Simultaneous translation of cRNA alpha and cRNA beta did not enhance membrane insertion of either the alpha or beta polypeptide.